Perspektif Remaja Tentang Kehamilan Usia Muda di Rumah Bersalin Karen Kabupaten Bekasi - Eka Mardiani Sari; Hikmah Ifayanti; Maulia Isnaini; Ririn Wulandari (Journal of Innovative and Creativity, 2025)
Teenage pregnancy is a reproductive health concern that affects the health, education, and psychological well-being of teenagers. Early pregnancy puts adolescents at risk for health issues, social disapproval, and dropping out of school. In order to investigate their opinions, experiences, and difficulties, it is essential to comprehend how adolescents regard teen pregnancy. The goal of this study is to offer comprehensive insights to aid in the creation of preventative measures and educational initiatives that are more successful. The research objective was to describe adolescents' perspectives on young pregnancy at the Karen Maternity Hospital in Bekasi Regency. The research design used was descriptive qualitative. The sample consisted of eight adolescents aged 15-19 years old, selected using purposive sampling. Data analysis was conducted through interview transcripts and qualitative research interpretation. According to the study's findings, the majority of teenage opinions about the causes of early pregnancy are influenced by free association; pregnancy happens because it is unplanned, which can interfere with continuing education and cause delays in entering the workforce; most teenagers date young; parents typically have a negative attitude towards unmarried pregnancy; and early pregnancy does not significantly harm a pregnant woman's physical health. It is anticipated that health professionals would take a more active role in educating teenagers about sexuality in a comprehensive and age-appropriate manner.